Control-value appraisals, achievement emotions, and foreign language performance: A latent interaction analysis. (October 2020) - Shao, Kaiqi; Pekrun, Reinhard; Marsh, Herbert W.; Loderer, Kristina
Abstract: Based on control-value theory (CVT), this study ( N  = 550 Chinese university students) examined relations between control-value appraisals, subsequent achievement emotions, and resulting performance in foreign language (FL) learning. The results show that perceived control and value related positively to positive emotions (enjoyment, hope, pride) and FL performance, and negatively to negative emotions (anger, anxiety, shame, hopelessness, boredom). Control and value interacted in predicting all eight emotions and FL performance. The multiplicative impact of the appraisals on performance was mediated by four of the focal emotions. These findings elucidate the impact of appraisals and emotions on achievement and support the generalizability of CVT to foreign language learning. Directions for future research and implications for education are discussed. Highlights: Control-value appraisals positively predict positive emotions and performance. These appraisals negatively predict students' negative emotions. The interaction between control and value significantly adds to the prediction. Emotions mediate the link between appraisals and performance. Teachers should attend to students' perceptions of academic control and value.